Immunomodulatory Effects of Vitamin D and Vitamin C to Improve Immunity in COVID-19 Patients - Yaqinuddin, Ahmed; Ambia, Ayesha Rahman; Alaujan, Raghad A. (Journal of Health and Allied Sciences NU, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-COV2) infection causes life-threatening respiratory illness, which has caused significant mortality and morbidity around the globe. Coronavirus disease 2019 (COVID-19) causes mild respiratory illness in most infected individuals; however, in some patients it may progress to sepsis, acute respiratory distress syndrome (ARDS), cytokine release syndrome (CRS), and multiorgan dysfunction (MODS), which results in intensive care unit (ICU) admissions and increased fatalities. Recent evidence shows that most of these comorbidities associated with COVID-19 infection are associated with dysregulation of the host immune response. Vitamins C and D have been shown to regulate immune response by decreasing the proinflammatory cytokine release from immune cells and inducing proliferation of other immune cells to robustly fight infection. This review critically evaluates the current literature on vitamins C and D in modulating an immune response in different diseases and their potential therapeutic effects in preventing complications in COVID-19 infection.
Keywords: vitamin C; vitamin D; COVID-19; immune response; chronic diseases